2011
DOI: 10.1021/ac102989n
|View full text |Cite
|
Sign up to set email alerts
|

Application of Photonic Crystal Enhanced Fluorescence to Cancer Biomarker Microarrays

Abstract: We report on the use of photonic crystal surfaces as a high-sensitivity platform for detection of a panel of cancer biomarkers in a protein microarray format. The photonic crystal surface is designed to provide an optical resonance at the excitation wavelength of cyanine-5 (Cy5), thus providing an increase in fluorescent intensity for Cy5-labeled analytes measured with a confocal microarray scanner, compared to a glass surface. The sandwich enzyme-linked immunosorbent assay (ELISA) is undertaken on a microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 34 publications
1
93
0
Order By: Relevance
“…10 These biosensors based on the labeling of biomolecules with tags, such as radioactive isotope, quantum dots or fluorescent dyes, have been applied for the detection of disease biomarkers. [11][12][13][14] Although these label-based methods have good sensitivity, they suffer from some drawbacks, including challenges concerning the labeling procedures, tedious and time-consuming experimental procedures, thereby hindering them from more extensive applications. 15 In an attempt to overcome the above disadvantages, several label-free sensor technologies have been employed to detect biomarkers, such as surface plasmon resonance (SPR), 16 a quartz crystal microbalance (QCM), 17 atomic force microscopy (AFM), 18 surface-enhanced raman spectroscopy (SERS), 19 and a fieldeffect transistor (FET).…”
Section: Introductionmentioning
confidence: 99%
“…10 These biosensors based on the labeling of biomolecules with tags, such as radioactive isotope, quantum dots or fluorescent dyes, have been applied for the detection of disease biomarkers. [11][12][13][14] Although these label-based methods have good sensitivity, they suffer from some drawbacks, including challenges concerning the labeling procedures, tedious and time-consuming experimental procedures, thereby hindering them from more extensive applications. 15 In an attempt to overcome the above disadvantages, several label-free sensor technologies have been employed to detect biomarkers, such as surface plasmon resonance (SPR), 16 a quartz crystal microbalance (QCM), 17 atomic force microscopy (AFM), 18 surface-enhanced raman spectroscopy (SERS), 19 and a fieldeffect transistor (FET).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report with PCEF slides has suggested that their range is from 0.3 pg mL 21 to 10 ng mL 21 (Huang et al, 2011;Cunningham and Zangar, 2012). With total seed protein at 25 mg mL 21 in our assays and lectin representing approximately 1% of the total extractable seed protein (Pull et al, 1978), the estimated amount of lectin in the solution is about 250 ng mL…”
Section: Discussion Abundant Proteins In Crude Extracts Saturate the mentioning
confidence: 75%
“…The incubation protocol was adapted from Huang et al (2011). Arrays were generally incubated within 1 week of being printed.…”
Section: Printing Of Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Recent years, optical detection methods based on the effect of guided-mode resonance are often used in biological testing. For example, optical devices combined with micro-nano structures based on this theory have been used in cancer detection, 8,9 serum concentrations of human IgE antibodies detection, 10 and live cell adhesion imaging. [11][12][13] In addition to these biological applications, guided-mode resonance methods can also be used to measure the refractive index of solutions.…”
Section: Introductionmentioning
confidence: 99%